Systems biology in biotech & pharma a changing paradigm - Prokop, Ales (SpringerBriefs in Pharmaceutical Science & Drug Development, 2012)
Systems Biology (SB) is a suite of technologies and methodologies that resulted, conceptually from the merging of two basic paradigms, reductionism and holism. It represents a combination of reductionist and holistic approaches to the relationships among the elements of a system, with the goal of identifying its emergent properties and defining, quantitatively, molecular, cellular, tissue, organ and whole body processes. One manifestation of SB is as a tool for hypothesis generation about a system that is typically too large and complex to understand by simple reasoning.